Nursing practice towards crack and other drugs from the perspective of nursing students - Fernanda Matos Fernandes Castelo Branco; Claudete Ferreira de Souza Monteiro (Revista de Pesquisa Cuidado é Fundamental Online)
Objective: The objective was to discuss how to act in front of the crack and other drugs from the perspective of nursing students. Methods: We applied the methodology of action research with fourteen nursing students in a University Center in the city of Teresina-PI, held in the month from March to November 2012. Results: The lines show a professional performance with an empirical basis, the majority of scientific information without imprint and information from media and information systems. Conclusion: reflecting the need for more knowledge about the issue as they will be future nurses who will work with this theme. Descriptors: Training of human resources in health. Illicit drugs. Nursing students.